1970
DOI: 10.1172/jci106322
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic ventilatory drive in normal man

Abstract: A B S T R A C TFor purposes of quantitation these curves are approximated by a simple hyperbolic function, the parameters of which are evaluated by a least squares fit of the data. The parameter A denotes curve shape such that the higher the value of A, the greater the increase in ventilation for a given decrease in PAO2 and hence the greater the hypoxic drive. Curves are highly reproducible for each subject and curves from different subjects are similar. In 10 normal subjects at resting PAcO2, A = 180.2 +14.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
176
2
6

Year Published

1979
1979
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 382 publications
(188 citation statements)
references
References 32 publications
4
176
2
6
Order By: Relevance
“…Next, hypoxaemia was induced by the method of Well, et al 5 Inhaled oxygen was gradually replaced with air and then with a mixture of air and nitrogen, so that end-tidal oxygen decreased to 5.3-6.0 kPa (40-45 tort) over an 8-10 minute period. End-tidal carbon dioxide concentration was monitored continuously and carbon dioxide was added directly to inhaled gas if necessary to maintain end-tidal isocapnia.…”
Section: Methodsmentioning
confidence: 99%
“…Next, hypoxaemia was induced by the method of Well, et al 5 Inhaled oxygen was gradually replaced with air and then with a mixture of air and nitrogen, so that end-tidal oxygen decreased to 5.3-6.0 kPa (40-45 tort) over an 8-10 minute period. End-tidal carbon dioxide concentration was monitored continuously and carbon dioxide was added directly to inhaled gas if necessary to maintain end-tidal isocapnia.…”
Section: Methodsmentioning
confidence: 99%
“…It has also been established that respiratory drive derives from detection of high carbon dioxide levels by peripheral chemoreceptors and receptors in the medulla [10]. There is also the theory of hypoxic drive, a form of respiratory drive, in which the medulla detects low levels of oxygen rather than high levels of carbon dioxide, resulting in the drive to breathe [11]. Hypoxic drive was thought to occur in patients with chronically elevated levels of CO 2 , such as patients with chronic obstructive pulmonary disease (COPD), but recent studies have shown that patients with COPD do not rely on hypoxic drive to breathe [12].…”
Section: Respiratory Drivementioning
confidence: 99%
“…Early methods (Richardson et al, 1966;Weil et al, 1970) (Slessarev et al, 2007). Prospective end-tidal targeting makes use of a gas-blending device, called the RespirAct™, in combination with a modified sequential gas delivery system.…”
Section: Using Prospective End-tidal Targeting To Measure the Odc In mentioning
confidence: 99%